Financial fragility of urban households in Malaysia - Selamah Abdullah Yusof,; Rohaiza Abd Rokis,; Wan Jamaliah Wan Jusoh, (Penerbit Universiti Kebangsaan Malaysia, 2015)
Household debt in Malaysia has been on an upward trend and increasing at a relatively fast pace. This study provides an in-depth micro analysis of the current Malaysian urban households’ vulnerabilities by examining the extent of their ability in dealing with financial shocks and factors that attribute to their financial fragility. Using a recent strictly random sample, it is found that Malaysian urban households are financially vulnerable. Only 10 percent of the households are resilient to shocks related to unemployment, physical disability, divorce, death, or changes in interest rate or stock market. More than a fifth of the households are not able to survive for at least three months if their income is cut off. Additionally, more than a fifth of these households do not have enough savings or any other source to turn to if there is a need to raise RM10,000 within a short period. Household income significantly affects a household current financial situation, while those with better financial knowledge and higher levels of education are less likely to be in asset poverty. The inability to cope with financial shocks differs across ethnic groups partly due to the wealth disparity and access to sources of funds. Initiatives must be undertaken to assist the households in facing these challenges and for them to exercise financial prudence. Additionally, household debt must be closely monitored to ensure that it is sustainable.